2004
DOI: 10.1128/mcb.24.18.8069-8079.2004
|View full text |Cite
|
Sign up to set email alerts
|

Sgt1 Associates with Hsp90: an Initial Step of Assembly of the Core Kinetochore Complex

Abstract: The kinetochore, which consists of DNA sequence elements and structural proteins, is essential for highfidelity chromosome transmission during cell division. In budding yeast, Sgt1, together with Skp1, is required for assembly of the core kinetochore complex (CBF3) via Ctf13 activation. Formation of the active Ctf13-Skp1 complex also requires Hsp90, a molecular chaperone. We have found that Sgt1 interacts with Hsp90 in yeast. We also have determined that Skp1 and Hsc82 (a yeast Hsp90 protein) bind to the N-ter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
114
1
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(118 citation statements)
references
References 50 publications
2
114
1
1
Order By: Relevance
“…First, it is clear that SGT1 is able to interact directly with HSP90 even in the absence of RAR1 ( Figure 9A), as shown by the yeast two-hybrid analysis and in vitro pull-down assays. Consistent with this, SGT1 interacts with HSP90 in yeast, which does not contain any RAR1 homologs (Bansal et al, 2004). The fact that the HSP90 interaction surface of the CS domain, but not that of RAR1, is highly conserved in eukaryotes also supports this notion.…”
Section: Rar1 Functions To Enhance the Hsp90-sgt1 Interactionsupporting
confidence: 60%
See 2 more Smart Citations
“…First, it is clear that SGT1 is able to interact directly with HSP90 even in the absence of RAR1 ( Figure 9A), as shown by the yeast two-hybrid analysis and in vitro pull-down assays. Consistent with this, SGT1 interacts with HSP90 in yeast, which does not contain any RAR1 homologs (Bansal et al, 2004). The fact that the HSP90 interaction surface of the CS domain, but not that of RAR1, is highly conserved in eukaryotes also supports this notion.…”
Section: Rar1 Functions To Enhance the Hsp90-sgt1 Interactionsupporting
confidence: 60%
“…Like HSP90, both SGT1 and RAR1 are required for the stabilization of many R proteins (Tornero et al, 2002;Bieri et al, 2004;Azevedo et al, 2006). Similarly, both HSP90 and SGT1 are required for the stabilization and assembly of the yeast CBF3 (for centromere binding factor3) and the human kinetochore complexes (Bansal et al, 2004;Lingelbach and Kaplan, 2004;Steensgaard et al, 2004;Niikura et al, 2006). As yeast does not contain any RAR1 homolog, CBF3 complex assembly is a RAR1-independent process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the activation process was initially thought to require Ctf13 phosphorylation by a Skp1-interacting kinase , later work showed that phosphorylation is not required for CBF3 assembly on centromeres (Stemmann et al 2002). Instead, an Hsp90-Sgt1 co-chaperone complex binds to Skp1, which enhances Skp1 binding to Ctf13 (Stemmann et al 2002;Bansal et al 2004;Rodrigo-Brenni et al 2004). Hsp90 and Sgt1 are not core kinetochore components and only transiently associate with Ctf13.…”
Section: Inner Centromere Binding Proteinsmentioning
confidence: 99%
“…Sgt1 functions as an adaptor linking various target proteins to Hsp90 (27). The TPR domain of Sgt1 interacts with Skp1 in the context of the CBF3 kinetochore complex or SCF E3 ubiquitin ligase (31,32). In addition, through its SGS domain, Sgt1 can interact with many LRR (leucine rich repeat) -containing proteins, such as yeast adenylate cyclase Cdc35 (33), plant R proteins (27,34) and mammalian NLR (Nod-like receptor) proteins including Nod1 and Nalp3 (35)(36)(37).…”
Section: Co-chaperones Working As Adaptor Proteins For Client Proteinsmentioning
confidence: 99%